Perbuatan Melawan Hukum Persaingan Usaha dalam Penjualan Tabung Gas Oksigen di Tengah Pandemi Covid-19 (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
The activity of setting prices is a natural thing to do by business actors as one of the steps that must be taken in order to gain profits from the capital issued. However, this cannot be justified if the price fixing process has deviated from the laws and regulations and has caused losses to various parties which can cause unfair business competition environmental conditions. The practice of increasing prices unilaterally by oxygen gas cylinder business actors that exceeds the normal price is considered an unlawful act because it is not in accordance with the norms of decency in society that business actors should follow considering the conditions at that time there was a spike in positive cases of Covid and many people who needed it. medical aids in the form of oxygen gas cylinders. This study uses a normative juridical method. The results of the study explain that the actions of business actors in increasing prices are included as an agreement that is prohibited in Law concerning the Unfair Business Competition.